Biofungicide Activity of Datura stramonium Leaf Extract Against Phytopathogenic Fungi - DJAHRA, Ali Boutlelis; BENKADDOUR, Mounia; ZEGHIB, Khaoula; BENKHERARA, Salah; SHAIEB, Inas; GHANIA, Ahmed; BDIDA, Soumaia (University of Eloued جامعة الوادي, 2019)
The aim of this study is determination of polyphenol contents and biofungicide activity of crude extract of Datura stramonium. The results of extraction showed an important yield percentage of crud extract equal 25.22 % wherase, the polyphenol content of the extract was 657,0 (mg AGE/ml Ext). The In vitro biofungicide activity carried out by disk diffusion method, the biofungicide effect results performed with crude extract and Milraz WP 76 fungicide (Propineb 70%, Cymoxanil 6%) against fungal strains. The results appear that natural substances possess an antifungal power on the multiresistant germs responsible for infectious diseases for plants. Growth inhibition varies depending on the fungal strains and the concentration of the test product
Articale in International Journal of biological and Agricultural Research Vol. 02 N. 01
Keywords: Datura stramonium, Milraz WP 76, Propineb, Cymoxanil, Biofungicide activity